Flexible Yttrium Coordination Geometry Inhibits “Bare-Metal” Guest Interactions in the Metal-Organic Framework Y(btc) - Josie E. Auckett; Stephen H. Ogilvie; Samuel G. Duyker; Peter D. Southon; Cameron J. Kepert; Vanessa K. Peterson (Energies, 2016)
Y(btc) (btc = 1,3,5-benzenetricarboxylate) is a metal-organic framework that exhibits significant adsorption of industrially-relevant gases such as H2, CH4, and O2. Previous studies have noted a surprising lack of close interactions between the adsorbed guest molecules and Y, despite the apparent availability of a “bare-metal” binding site. We have extended our previous work in a detailed investigation of the adsorption behaviours of CO2, CD4, and O2 in Y(btc) over a range of concentrations using in situ neutron powder diffraction methods. The O–Y–O bond angles enclosing the bare-metal site are found to change considerably depending on the type and quantity of guest molecules present. Multiple binding sites are found for each guest species, and the largest changes in O–Y–O angles are accompanied by changes in the filling sequences of the binding sites, pointing to an important interplay between guest-induced framework distortions and binding site accessibility. These results suggest the potential for coordinatively flexible rare-earth metal centres to promote guest-selective binding in metal-organic frameworks.